2018
DOI: 10.2147/copd.s166163
|View full text |Cite
|
Sign up to set email alerts
|

COPD phenotypes: differences in survival

Abstract: BackgroundThe aim of the study was to analyze the characteristics and survival of a group of patients with COPD according to their clinical phenotype.Patients and methodsThe study population was selected from patients undergoing scheduled spirometry between January 1, 2011 and June 30, 2011 at the respiratory function laboratory of a teaching hospital and comprised those with a previous and confirmed diagnosis of COPD and forced expiratory volume in the first second (FEV1) of <70%. The patients selected were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
5
9
0
Order By: Relevance
“…In a recent study from Spain, the authors demonstrated that the Spanish ACO and NE phenotypes were associated with a more favourable outcome when compared to the two exacerbator phenotypes. 12 , 18 This is in full accordance with our results that showed similar patterns of mortality risk when using “Spanish” phenotypes as COPD classification. 12 , 18 , 19 Besides, our data showed similar mortality patterns also for the GOLD groups and stages.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study from Spain, the authors demonstrated that the Spanish ACO and NE phenotypes were associated with a more favourable outcome when compared to the two exacerbator phenotypes. 12 , 18 This is in full accordance with our results that showed similar patterns of mortality risk when using “Spanish” phenotypes as COPD classification. 12 , 18 , 19 Besides, our data showed similar mortality patterns also for the GOLD groups and stages.…”
Section: Discussionsupporting
confidence: 91%
“… 13 According to GesEPOC, a patient has asthma-COPD overlap (ACO) phenotype if they demonstrate a very positive response in the bronchodilator test, defined as an FEV1 increment greater than 400 mL in absolute value and 15% in relative value. Similar to other published studies, 15 we think that this definition provides very high specificity but little sensitivity for this phenotype. Instead of the ACO phenotype, we use the PRTB phenotype.…”
Section: Methodssupporting
confidence: 89%
“…The classification of COPD patients into different phenotypes is a recommendation that has been added to clinical practice guidelines in recent years, 13 , 14 since not all COPD patients clinically behave in the same way or present the same evolution. 15 Therefore, it is also interesting to investigate the influence of these comorbid conditions on each COPD phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in mortality was demonstrated for different phenotypes, although it is striking that no statistically significant differences were found for the exacerbator-with-chronic-bronchitis phenotype, possibly because this phenotype is associated with poorer survival than the other phenotypes [8]. In fact, we found that the Kaplan-Meier survival curve of patients with pneumonia having this phenotype was much lower than that of the group of patients without pneumonia at 18 months presenting the other phenotypes.…”
Section: Discussionmentioning
confidence: 55%
“…Chronic obstructive pulmonary disease (COPD) is a highly prevalent disease with elevated morbidity and mortality [6][7][8]. It is often accompanied by various comorbid conditions including arthritis, heart disease, arterial hypertension, diabetes mellitus, dyslipidemia, psychiatric disease, gastrointestinal disorders, cancer, and osteoporosis [9,10].…”
Section: Introductionmentioning
confidence: 99%